Comprehensive transcriptomic analysis unveils the interplay of mRNA and LncRNA expression in shaping collagen organization and skin development in Dezhou donkeys - Wang, Xinrui; Peng, Yongdong; Liang, Huili; Zahoor Khan, Muhammad; Ren, Wei; Huang, Bingjian; Chen, Yinghui; Xing, Shishuai; Zhan, Yandong; Wang, Changfa (Frontiers in Genetics, 2024)
The primary focus of donkey hide gelatin processing lies in the dermal layer of donkey hide due to its abundant collagen content. However, the molecular mechanism involved in collagen organization and skin development in donkey skin tissue across various developmental stages remains incomplete. The current study aims to investigate the transcriptomic screening of lncRNAs and mRNA associated with skin development and collagen organization across different ages in Dezhou donkeys’ skin. In the pursuit of this objective, we used nine skin tissue samples obtained from Dezhou donkeys at various ages including 8-month fetal stage, followed by 2 and 8 years. RNA-seq analysis was performed for the transcriptomic profiling of differentially expressed genes (DEGs) and lncRNAs associated with skin development in different age groups. Our investigation revealed the presence of 6,582, 6,455, and 405 differentially expressed genes and 654, 789, and 29 differentially expressed LncRNAs within the skin tissues of Dezhou donkeys when comparing young donkeys (YD) vs. middle-aged donkeys (MD), YD vs. old donkeys (OD), and MD vs. OD, respectively. Furthermore, we identified Collagen Type I Alpha 1 Chain (COL1A1), Collagen Type III Alpha 1 Chain (COL3A1), and Collagen Type VI Alpha 5 Chain (COL6A5) as key genes involved in collagen synthesis, with COL1A1 being subject to cis-regulation by several differentially expressed LncRNAs, including ENSEAST00005041187, ENSEAST00005038497, and MSTRG.17248.1, among others. Interestingly, collagen organizational and skin development linked pathways including Protein digestion and absorption, metabolic pathways, Phosphatidylinositol 3-Kinase-Protein Kinase B signaling pathway (PI3K-Akt signaling pathway), Extracellular Matrix-Receptor Interaction (ECM-receptor interaction), and Relaxin signaling were also reported across different age groups in Dezhou donkey skin. These findings enhance our comprehension of the molecular mechanisms underlying Dezhou donkey skin development and collagen biosynthesis and organization, thus furnishing a solid theoretical foundation for future research endeavors in this domain.